Thermal Stability and Sulfidizing Resistance of High Reflective Multilayered Sn/Ag3Sn and Sn/Ag Films Electrodeposited on Cu Alloy Sheets. (10th September 2016) - Kure-Chu, Song-Zhu; Ogasawara, Toru; Ye, Rong-bin; Yashiro, Hitoshi; Sasaki, Kuniaki
Abstract: We reported multilayered Sn/Ag3 Sn and Sn/Ag films with Ag thickness of 20–300 nm that electroplated on a reflowed Sn layer on Cu alloy sheets as promising coating materials for LED lead-frames. The morphology, surface roughness, crystalline structure, and reflectance of multilayered Sn/Ag-based films are more dependent on plating baths than on Ag thickness. The Sn/Ag3 Sn film obtained from a cyanide Ag bath exhibited high specular reflectivity of 65–70% (480 nm), whereas the Sn/Ag films from a cyanide-free bath showed a high total reflectivity of 94% similar to commercial Ag films. The reflectance of both the multilayered Sn/Ag3 Sn and Sn/Ag films almost unchanged even after heating at 373 K for 120 h, in comparison with the apparent drop for a commercial Ag film. Moreover, the multilayered Sn/Ag3 Sn films, both the as-deposited and the annealed specimens, remained the reflectivity even after immersing in a 0.2 ml/L (NH4 )2 Sx solution for 60 min. The excellent sulfidizing resistance of the Sn/Ag3 Sn films can be attributed to the chemically stable Ag3 Sn alloy layer with improved corrosion resistance and the protective SnO/SnO2 thin film on the surface, thus inhibiting the chemical reaction of Ag and S 2– ions.